2004
DOI: 10.1063/1.1776622
|View full text |Cite
|
Sign up to set email alerts
|

Additional phonon modes and close satellite valleys crucialfor electron transport in hexagonal gallium nitride

Abstract: Conventional models of electron transport in hexagonal GaN crystals predicting electron drift velocity peak value up to 3.2×107cm∕s at 140–220kV∕cm and a pronounced negative differential mobility at higher fields are revised. The new model is suggested accounting for the additional low-energy optical phonon modes (∼26meV) and the satellite valley location close (400meV) to the conduction band bottom. Electron scattering on these and conventional (∼92meV) LO-phonon modes together with the fast intervalley excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…It is particularly interesting to note that the arguments of Bulutay et al [258] add considerable credence to the earlier inflection point argument of Krishnamurthy et al [256]. In 2004, Brazis and Raguotis [259] reported on the results of a Monte Carlo study involving additional phonon modes and a smaller conduction band inter-valley energy separation for the case of wurtzite GaN. Their results were found to be much closer to the experimental results of Wraback et al [11] than those found previously.…”
Section: Electron Transport Within Gan: a Reviewsupporting
confidence: 58%
“…It is particularly interesting to note that the arguments of Bulutay et al [258] add considerable credence to the earlier inflection point argument of Krishnamurthy et al [256]. In 2004, Brazis and Raguotis [259] reported on the results of a Monte Carlo study involving additional phonon modes and a smaller conduction band inter-valley energy separation for the case of wurtzite GaN. Their results were found to be much closer to the experimental results of Wraback et al [11] than those found previously.…”
Section: Electron Transport Within Gan: a Reviewsupporting
confidence: 58%
“…A revised model has been proposed [5] and proved to be in excellent agreement with experimental drift velocity data [3]. In this paper we compare MC and experimental data on electron mobility obtained at room temperature (Fig.…”
Section: Effects Of Additional Phonons In Wurtzite Ganmentioning
confidence: 95%
“…We conclude that the additional phonon modes and close satellite valleys are crucial for electron transport in hexagonal GaN crystal [5]. Phonon accumu- lation is another interesting point becoming exceedingly important at low lattice temperatures.…”
Section: Effects Of Excess Phonons In Cubic Ganmentioning
confidence: 99%
See 1 more Smart Citation
“…the broadening activation energy (12 meV) appears to be consistent with low-energy acoustic phonon modes (17-39 meV range) [13,14]. It should be noted that Brazis and Raguotis found it necessary to include such low-energy phonon modes in their Monte Carlo study of electron transport in GaN [14], and that their results have been found to be much Electron mobility spectra extracted using HR-QMSA with a 50 points/decade mobility grid. Note the significant improvement in resolution and the broadening effect of temperature on the linewidth of the conductivity peaks.…”
Section: Resultsmentioning
confidence: 64%